Definition, Function, and Scope of Legal Drafting - Suwandi Suwandi; Muhammad Prian Dani (Program Pascasarjana UIN Sumatera Utara Medan, 2022)
Indonesia, as a nation governed by the rule of law, demands high-quality legal products to ensure legal certainty, justice, and the benefits of law in social and state life. However, in practice, various legal problems are still frequently encountered due to poor drafting of legal documents, such as regulations with multiple interpretations and unclear contracts. Therefore, this study aims to comprehensively examine the definition, function, and scope of legal drafting as an important basis for the formation of good legal documents. The research method used is normative legal research with a qualitative approach through library research, by reviewing various literature, journals, and the opinions of relevant experts. The results show that legal drafting is a process of preparing legal documents that requires precise language, clear systematics, and a deep understanding of legal substance. Legal drafting has an important function in creating legal certainty, regulating and controlling behavior, providing legal protection, and serving as a guideline for dispute resolution and a means of social engineering. The scope includes legislative drafting, contract drafting, regulatory drafting, and judicial drafting. In conclusion, good mastery of legal drafting is essential for legal students and practitioners to be able to produce quality, clear legal documents that do not give rise to multiple interpretations, thereby supporting the creation of an effective and just legal system.